Po tropach średniowiecznej kancelarii Zakonu Paulinów - Zbudniewek, Janusz (Vox Patrum, 2016)
The keeping of the scriptorium and chancery by the first Polish Paulines dates back to the first half of the 15th century. It was mainly focused on copying liturgical and related books used for pastoral purposes, legal documentation and history, which included among others the history of the image of Our Lady (Translacio tabule) and the Chronicle of Wincenty Kadłubek. In the 16th century the scriptorium of Jasna Góra undertook the documentation of religious life in the sanctuary, including the first reports of pilgrims and records of confreres, as a response to the attacks of the Reformation. At the same time the scriptorium created the first cartularies and other books containing legal processes, inventories, as well as library and account records. The development process of the chancery has reached its peak in the early 17th century, when Fr. Mikołaj Staszewski (1595-1658), a former employee of the Curia of Poznań, later Provincial and General of the Pauline Order, entered the Board of the Order and introduced a new style of copying files. He also initiated the process of writing Pauline chronicles – first of the Polish Province and then of the whole Order, and introduced relevant secretarial standards to the religious constitution, of which he was the main inspirer and contractor. Currently the Polish Pauline Archives store 71 medieval manuscripts from Polish scriptoria, and more than 40 cartulary books from the modern era, among which only one Formulare obedientiarum salutationum et epistolarum variarum of Dionizy Klękowski (1599-1675) contains 1053 copies of various documents and correspondence from the period 1367-1673.